Variation in the expression of ergot alkaloids between individual tillers of perennial ryegrass - Mace, Wade J.; Lunn, Kristy L.; Kaur, Navjot; Lloyd-West, Catherine M. (Frontiers in Chemistry, 2014)
Epichloë fungal endophytes of cool season grasses are well known to produce a range of alkaloids of benefit to the host. Some of these compounds are advantageous to agriculture due to qualities that promote pasture persistence (e.g. the loline class of alkaloids confer insect protection) while others are detrimental to the wellbeing of grazing livestock. The ergot alkaloids (e.g. ergovaline), produced in ryegrass and tall fescue associations, causes poor animal health in farming regions in many countries around the world and further study is required to improve our knowledge on this class of compounds. Here we present the application of a quantitative LC-MS/MS (liquid chromatography coupled to mass spectrometry) method measuring eight ergot alkaloids (chanoclavine, agroclavine, elymoclavine, lysergol, lysergic acid, ergine, lysergyl alanine, ergovaline) produced by endophyte infected grasses, to monitor levels in individual tillers from multiple plants of a single cultivar of perennial ryegrass (Lolium perenne cv. ‘Grasslands Samson’) infected with a common toxic endophyte strain (Epichloë festucae var. lolii). Monitoring the expression in individual tillers allows an estimation of the variability within a plant (between tillers) as well as between plants. The study showed that there is significant variation in the concentration of the ergot alkaloids between tillers of a single plant, at or exceeding the level of variation observed between individual plants of a population. This result emphasizes the fundamental importance of robust experimental design and sampling procedures when alkaloid expression assessment is required and these need to be rigorously tailored to the hypothesis being tested.